Development of Hydrogen Peroxide Biosensor Based on Immobilization of Hemoglobin on Screen-Printed Carbon Electrode Modified With Silver Nanoparticles - Elewi, Ali Saad; Wadood, Shatha Abdul; Ali, Abdul Kareem Mohammed (Iraqi Journal of Science, 2019)
The direct electron transfer behavior of hemoglobin that is immobilized onto screen-printed carbon electrode (SPCE) modified with silver nanoparticles (AgNPs) and chitosan (CS) was studied in this work. Cyclic voltametry and spectrophotometry were used to characterize the hemoglobin (Hb) bioconjunction with AgNPs and CS. Results of the modified electrode showed quasi-reversible redox peaks with a formal potential of (-0.245V) versus Ag/AgCl in 0.1M phosphate buffer solution (PBS), pH7, at a scan rate of 0.1Vs-1. The charge transfer coefficient (Î±) was 0.48 and the apparent electron transfer rate constant (Ks) was 0.47s-1. The electrode was used as a hydrogen peroxide biosensor with a linear response over 3 to 240 ÂµM and a detection limit of 0.6 ÂµM. As a result, the modified biosensor here has exhibited a high sensitivity, good reproducibility and stability.